2006
DOI: 10.1007/s11127-005-9002-z
|View full text |Cite
|
Sign up to set email alerts
|

Do supermajority rules limit or enhance majority tyranny? evidence from the US States, 1960–1997

Abstract: Buchanan and Tullock (1962) demonstrates that supermajority rules can reduce tyranny of majority problems in a democracy. However, recent theoretical work by Dixit, Grossman, and Gul (2000) postulates that this static analysis of supermajority rules may be inadequate to explain political decisions in a dynamic setting. In fact, supermajority rules may increase the incidence of majority tyranny because of rotating political representation. Using data from US state legislatures we examine the effect of supermajo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 15 publications
(16 reference statements)
0
48
0
Order By: Relevance
“…In a simple legislative bargaining model, claimed that supermajority requirements to approve tax increases allow government to reduce taxes by delegating taxing power to a pivotal voter who prefers lower taxes. Using data from U.S. state legislatures, and ) found that supermajority rule is indeed associated with lower tax rates and less spending on public welfare, respectively. In a panel of 50 states from 1970 to 2008, showed that supermajority rule lowers redistributive taxes targeted toward narrow groups.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a simple legislative bargaining model, claimed that supermajority requirements to approve tax increases allow government to reduce taxes by delegating taxing power to a pivotal voter who prefers lower taxes. Using data from U.S. state legislatures, and ) found that supermajority rule is indeed associated with lower tax rates and less spending on public welfare, respectively. In a panel of 50 states from 1970 to 2008, showed that supermajority rule lowers redistributive taxes targeted toward narrow groups.…”
Section: Introductionmentioning
confidence: 97%
“…Choice among voting rules, from a simple majority to unanimity, is said to critically influence budget allocation by altering the distribution of voting powers among different coalitions (; ; ). This article investigates the hypothesis that supermajority rule may increase the size of public spending and taxation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two-thirds requirement to pass the budget empowers the minority party, particularly when trying to raise taxes or, more generally, change the status quo (Knight 2000; but see Bradbury and Johnson 2006;McGann 2004). This can only truly matter if the minority party is sufficiently large and cohesive enough on budget matters.…”
Section: Consequences Of Partisan Polarizationmentioning
confidence: 99%
“…16. See Bohn and Inman (1996), Crain and Miller (1990), Knight (2001), Bradbury and Johnson (2002), and Crain (2003). 17.…”
Section: Concluding Commentsmentioning
confidence: 99%